Expression analysis and characterization of resistance (R) genes in contrasting Fusarium wilt resistant chickpea genotypes - Zahid, Muhammad Salman; Nawaz, Muhammad Amjad; Tanveer, Muhammad Huzaifa; Shahzadi, Saman; Fayyaz, Maria; Shafique, Ikhlas; Abbas, Amjad (Integrative Plant Biotechnology, 2023)
Fusarium wilt is one of the most notorious diseases of crop plants. This disease leads to huge crop losses in chickpea with substantial monetary value worldwide. The objective of the current study was to characterise Fusarium oxysporum f. sp. cicris (Foc), the causal agent of chickpea wilt, on morphological basis followed by the assessment of resistance of thirty chickpea germplasm accessions to Foc in a pot experiment. The second objective of this research was to study gene expression and characterisation of specific resistance (R) genes in different Fusarium wilt-resistant chickpea genotypes. The morphological identification and characterization of Foc was done by culturing the fungus potato dextrose agar (PDA) medium. Fusarium wild resistance was assessed by challenging 30 chickpea genotypes to artificial inoculum of Foc by using a pre-defined disease rating scale. Different resistance levels were showed by different chickpea genotypes ranging from highly resistant to highly susceptible. Two accessions demonstrated resistance, 15 were moderately resistant and the rest of the genotypes were moderately susceptible to susceptible. The in-silico expression analysis of R genes showed that two R genes, LOC101499430 and LOC101499568 were upregulated in chickpea roots, indicating their probable role in Fusarium wilt resistance. The genes were further assessed for their expression in response to Fusarium inoculation in contrasting Fusarium wilt resistant and susceptible chickpea genotypes. The resistant genotypes showed significantly higher expression levels of the selected R genes in comparison with susceptible genotypes. This study provides valuable insights into evaluating chickpea germplasm for Fusarium wilt resistance and identification of candidate resistance genes which could be employed for enhancement of Fusarium wilt resistance in chickpea.
Keywords: Resistance (R) genes; R gene; Fusarium wilt; Chickpea; Expression analysis